Strategi Kepemimpinan Kepala Sekolah dalam Mengembangkan Mutu Pendidikan Melalui Manajemen Berbasis Sekolah di SDN Aceh Besar - Marlina, Cut Leni; Rahmatullah, Rahmatullah; Musdiani, Musdiani; Sari, Siti Mayang (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to determine the influence of the principal's leadership strategy in developing the quality of education, through school-based management. The research conducted used quantitative and qualitative approaches. The population in this study amounted to 165 people, the sample taken was 64 people. The data collection techniques used in this study consisted of questionnaires, interviews, observations, and documentation. Data analysis techniques use data collection, data reduction, data presentation to determine the influence between variables of principal leadership strategy (X1), school-based management (X2) and education quality (Y). The results of the study were the influence of the principal's leadership strategy in developing the quality of education at SDN Aceh Besar with a percentage of 56.7%, there was the influence of school-based management on the quality of education at SDN Aceh Besar with a percentage of 47.9%, there was the influence of the principal's leadership strategy in developing the quality of education through school-based management at SDN Aceh Besar with a percentage of 77.3%.